2015
DOI: 10.5194/bg-12-3861-2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CO<sub>2</sub>-driven ocean acidification on early life stages of marine medaka (<i>Oryzias melastigma</i>)

Abstract: Abstract. The potential effects of high CO 2 and associated ocean acidification (OA) in marine fishes and other noncalcified organisms are less well understood. In this study, we investigated the responses of early life stages (ELS) of marine medaka (Oryzias melastigma) exposed to a series of experimental manipulation of CO 2 levels. Results showed that CO 2 -driven seawater acidification (pH 7.6 and pH 7.2) had no detectable effect on hatching time, hatching rate, or heart rate of embryos. However, the deform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…(Depasquale et al 2015;Mu et al 2015). While taxonomically diverse, these examples all represent species that reproduce in very shallow, nearshore waters with likely large short-term CO 2 fluctuations to which they must be adapted.Slightly greater CO 2 sensitivities, on the other hand, appear to exist for coastal shelf species including Atlantic cod (Gadus morhua Linnaeus 1758,Stiasny et al 2016;Stiasny et al 2018), summer flounder (Paralichthys dentatus Linnaeus 1766,Chambers et al 2014) or Senegalese sole (Solea senegalensis Kaup 1858,Pimentel et al 2014b), …”
mentioning
confidence: 99%
“…(Depasquale et al 2015;Mu et al 2015). While taxonomically diverse, these examples all represent species that reproduce in very shallow, nearshore waters with likely large short-term CO 2 fluctuations to which they must be adapted.Slightly greater CO 2 sensitivities, on the other hand, appear to exist for coastal shelf species including Atlantic cod (Gadus morhua Linnaeus 1758,Stiasny et al 2016;Stiasny et al 2018), summer flounder (Paralichthys dentatus Linnaeus 1766,Chambers et al 2014) or Senegalese sole (Solea senegalensis Kaup 1858,Pimentel et al 2014b), …”
mentioning
confidence: 99%
“…As such, it is often informative to investigate each otolith independently rather than investigating one type or pooling by type without regard to side. Among the 24 studies reviewed here that analyzed ocean acidification impacts on otolith morphology, five investigated lapilli (Table 1), none investigated asterisci, and eight segregated otoliths by side during morphometric analysis (at least six of which pooled them after observing no evidence of asymmetry) (Franke & Clemmesen, 2011; Munday et al, 2011a; Munday et al, 2011b; Maneja et al, 2013; Bignami, Sponaugle & Cowen, 2014; Mu et al, 2015; Perry et al, 2015; Réveillac et al, 2015; Martins, 2017; Jarrold & Munday, 2018). However, the results suggest that responses of one or two otoliths cannot necessarily be extrapolated to the rest of the otolith system.…”
Section: Discussionmentioning
confidence: 99%
“…This growth is attributed to elevated blood plasma [HCO], retained to buffer acidosis and transported into the endolymph where it becomes substrate for CO aggregation (Checkley et al, 2009; Munday et al, 2011b; Heuer & Grosell, 2014). Only one study (Mu et al, 2015) observed decreased otolith size in response to elevated pCO 2 . Other studies (Franke & Clemmesen, 2011; Munday et al, 2011a; Simpson et al, 2011; Frommel et al, 2013; Perry et al, 2015; Cattano et al, 2017; Martino et al, 2017; Jarrold & Munday, 2018) observed no effects of pCO 2 on otolith morphology.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in otolith size was revealed in a range of species following exposure to as little as 64 µatm of additional CO 2 compared to control levels of CO 2 , in species such as sea bass larvae (Atractoscion nobilis) (Checkley et al, 2009), clownfish (A. percula) larvae (Munday et al, 2011b), juvenile walleye Pollock (Theragra chalcogramma) (Hurst et al, 2012), cobia (Rachycentron canadum) larvae (Bignami et al, 2013a,b), cod (Gadus morhua) larvae (Frommel et al, 2012;Maneja et al, 2013), juvenile sticklebacks (Gasterosteus aculeatus) (Schade et al, 2014), mahi-mahi (Coryphaena hippurus) larvae (Bignami et al, 2014), juvenile sea bream (Sparus aurata) (Réveillac et al, 2015), and mulloway (Argyrosomus japonicus) larvae (Rossi et al, 2016b). However, the otoliths of juvenile spiny damselfish (Acanthochromis polyacanthus) (Munday et al, 2011a), juvenile clownfish (A. percula) (Simpson et al, 2011), Atlantic herring (Clupea harengus) larvae (Franke and Clemmesen, 2011), and juvenile scup (Stenotomus chrysops, (Perry et al, 2015) showed no size differences at increased levels of CO 2 , whereas the size of the otoliths in marine medaka larvae, Oryzias melastigma, were even observed to be reduced (Mu et al, 2015). This reveals that the deposition and chemical composition of fish otoliths is dependent on CO 2 levels, and that the effects may be variable (depending on ocean acidification conditions), speciesspecific, and sensitive to the duration of the study.…”
Section: Ocean Acidification and Auditory Impairmentmentioning
confidence: 99%